Adoption of municipal bylaw legislating mandatory helmet use for cyclists under the age of 18: impact on cycling and helmet use - Aurélie Maurice; Michel Lavoie; Denis Hamel; Mylène Riva (Health Promotion and Chronic Disease Prevention in Canada, 2020)
Introduction: Bicycle helmet use is recognized as an effective way to prevent head injuries in cyclists. A number of countries have introduced legislation to make helmets mandatory, but many object to this type of measure for fear that it could discourage people, particularly teenagers, from cycling. In 2011, the City of Sherbrooke adopted a bylaw requiring minors to wear a bicycle helmet. The objective of this study was to assess the impact of this bylaw on cycling and bicycle helmet use. Methods: The impact of the bylaw was measured by comparing the evolution of bicycle helmet use among youth aged 12 to 17 years in the Sherbrooke area (n = 248) and in three control regions (n = 767), through the use of logistic regression analyses. Results: Cycling rates remained stable in the Sherbrooke area (going from 49.9% to 53.8%) but decreased in the control regions (going from 59.1% to 46.3%). This difference in evolution shows that cycling rates increased in the Sherbrooke area after the adoption of the bylaw, compared to the control regions (odds ratio [OR] of the interaction term: 2.32; 95% confidence interval [CI]: 1.01–5.35). With respect to helmet use, a non–statistically significant upward trend was observed in the Sherbrooke area (going from 43.5% to 60.6%). This figure remained stable in the control regions (going from 41.5% to 41.9%). No significant difference was observed in the evolution of helmet use between the two groups (OR of the interaction term of 2.70; 95% CI: 0.67–10.83). Conclusion: After the bylaw was adopted, bicycle use among youth aged 12 to 17 years in the Sherbrooke area remained stable and helmet used increased, though not significantly.